Gender Differences in Social Emotional Learning (SEL) Ability: A Cross-Sectional Study in Adolescents in Indonesia - Budi Astuti; Rizqi Lestari; Salma Salsabila Hasna; Natri Sutanti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to analyze gender differences in Social-Emotional Learning (SEL) abilities among adolescents in Yogyakarta, Indonesia. Using a cross-sectional approach, 521 adolescents (230 boys and 291 girls) aged 15–18 years participated in this study. The research instruments used have been culturally adapted to measure the five dimensions of SEL: emotion regulation, empathy, cooperation, leadership, and stress resilience. Data analysis using independent samples t-test and MANOVA showed that adolescent girls were significantly superior in emotion regulation (p < 0.001), empathy (p < 0.001), and cooperation (p = 0.002), while adolescent boys were better at leadership (p < 0.001) and stress resilience (p < 0.001). These findings indicate that gender differences in SEL are influenced by biological factors and Javanese social and cultural norms typical of Yogyakarta, where women are encouraged to be more empathetic and harmonious. At the same time, men are expected to be more independent and resilient. The study's implications emphasize the importance of developing SEL programs that are responsive to gender and local contexts, such as stress-management training for women and increased empathy and cooperation for men. Thus, appropriate interventions can more holistically support adolescent social-emotional development.  Keywords: social emotional learning, gender differences, adolescents, yogyakarta, javanese culture